Sub-national government and pathways to sustainable energy. (November 2017) - Cowell, Richard; Ellis, Geraint; Sherry-Brennan, Fionnguala; Strachan, Peter A; Toke, David
In an effort to understand how to promote more sustainable forms of energy provision, researchers have begun addressing the scale of political and governance processes, yet the effects of sub-national government remain neglected. At the same time, analysts of political devolution, decentralisation and independence have rarely given attention to the energy sector. Papers in this special issue seek to better understand the relationship between sub-national government and pathways to sustainable energy: examining how city-regional and devolved governments have shaped agendas for building retrofit; elucidating the importance of decentralised governance in knitting together electricity, heat and transport energy markets; mapping the complex, fuzzy spatial organisation of legal powers to direct energy policy across multi-level polities; and analysing conflicts over the allocation of energy infrastructure consenting powers between national and devolved governments. The papers highlight the interdependencies of action in different governmental arenas, and reinforce arguments for greater central-to-local reflexivity in governance styles. Analysing the interface between sub-national government and energy transition also raises new questions about the meaning of 'sovereignty', the fragmentary nature of democratic control over energy systems, and the effects of boundaries.